REGULATION AND FINANCING OF ENVIRONMENTAL PROGRAMS: DEVELOPMENT OF PUBLIC-PRIVATE PARTNERSHIPS IN THE DIGITAL ECONOMY - Alekseev, Evgeny; Pinkovskaya, Galina; Ustinova, Yuliya; Ermolaeva, Evgeniya; Romanishina, Tatyana (Revista Inclusiones, 2020)
The need to ensure sustainable growth in the standard of living of the population through the introduction of environmentally oriented programs and projects makes all the institutions of socioeconomic relations more active. For the implementation of environmentally oriented programs and projects, one of the important tasks of environmental policy is the harmonization of environmental and economic relations. As a result, it necessary to search for effective and competitive forms of solidarity regulation and financing of such programs and projects, which provide for close interaction of the business sector, government authorities and society. The study provides a theoretical analysis of the concept of public-private partnership. Based on an expert survey, the forms of public-private partnership, the main expected effects from the implementation of public-private partnership mechanisms and the criteria for its application in the implementation of environmental programs and projects are determined. Foreign experience in the application of various forms of public-private partnership in the environmental sphere is analyzed.